Role of the Vnn1 pantetheinase in tissue tolerance to stress. (11th August 2014) - Naquet, Philippe; Pitari, Giuseppina; Duprè, Sylvestro; Galland, Franck
Abstract : Pantetheinase is an ubiquitous enzyme which hydrolyses D -pantetheine into cysteamine and pantothenate (vitamin B5 ) on the dissimilative pathway of CoA. Pantetheinase isoforms are encoded by the Vnn (vanin) genes and Vnn1 is the predominant tissue isoform in mice and humans. In the present article, we review the results showing the regulation of Vnn1 expression during developmental, repair and inflammatory situations and the impact of a Vnn1 deficiency in mouse models of pathologies. We document the involvement of the Vnn1 pantetheinase in situations of increased tissue needs and propose that Vnn1 through recycling of pantothenate and release of cysteamine in tissues participates in the adaptive response of the tissue to stress.